One Woman in a Hundred : Edna Phillips and the Philadelphia Orchestra - Welsh, Mary Sue (Book collections on Project MUSE., 2013)
Gifted harpist Edna Phillips (1907-2003) joined the Philadelphia Orchestra in 1930, becoming not only that ensemble's first female member but also the first woman to hold a principal position in a major American orchestra. Plucked from the Curtis Institute of Music in the midst of her studies, Phillips was only twenty-three years old when Leopold Stokowski, one of the twentieth century's most innovative and controversial conductors, named her principal harpist. This candid account traces Phillips's journey through the competitive realm of Philadelphia's virtuoso players, where she survived - and thrived - thanks to her undeniable talent, determination, and lively humor. Drawing on extensive interviews with Phillips, her family, and colleagues, as well as archival sources, this book chronicles the training, aspirations, setbacks, and successes of this pioneering woman musician. The author recounts numerous insider stories of rehearsal and performance with Stokowski and other renowned conductors of the period such as Arturo Toscanini, Fritz Reiner, Otto Klemperer, Sir Thomas Beecham, and Eugene Ormandy. She also depicts Phillips's interactions with fellow performers, the orchestra management, and her teacher, the wily and brilliant Carlos Salzedo. Blessed with a nimble wit, Phillips navigated a plethora of challenges, ranging from false conductors' cues to the advances of the debonair Stokowski and others. She remained with the orchestra through some of its most exciting years from 1930 to 1946 and was instrumental in fostering harp performance, commissioning many significant contributions to the literature. This portrait of Phillips's exceptional tenure with the Philadelphia Orchestra also reveals the behind-the-scenes life of a famous orchestra during a period in which Rachmaninoff declared it "the finest orchestra the world has ever heard." Through Phillips's perceptive eyes, readers will watch as Stokowski melds his musicians into a marvelously flexible ensemble; world-class performers reach great heights and make embarrassing flubs; Greta Garbo comes to Philadelphia to observe her lover Leopold Stokowski at work; and the orchestra encounters the novel experience of recording for Walt Disney's Fantasia. A colorful glimpse into a world-class orchestra at the height of its glory, this book tells the fascinating story of a woman brave enough and strong enough to overcome historic barriers and pursue her dreams. -- Book jacket.